Coordination, Cost, and Changing Epidemiology—Considerations in the Hepatitis C Care Cascade. Issue 3 (28th February 2021) - Yang, Nancy; Muir, Andrew
Abstract : This editorial reviews two articles in Hepatology Communications addressing challenges in the hepatitis C care cascade.